Engineering non-Hermitian skin effect with band topology in ultracold gases - Lihong Zhou; Haowei Li; Wei Yi; Xiaoling Cui (Communications Physics, 2022)
The non-Hermitian skin effect comprises of boundary localised eigenmodes and has been realised in a range of 1D systems such as photonics and metamaterials. Here, the authors achieve the same effect in a quantum many-body setting using ultra-cold gases and, by tuning the strength of the spin orbit coupling, realise a non-trivial band topology.